“WHO IS CHRIST FOR US TODAY?” BONHOEFFER’S QUESTION FOR THE CHURCH - Henco Van der Westhuizen (Acta Theologica)
How can a theology thinking about the church learn from Bonhoeffer’s famous and oft repeated question of who Jesus Christ is for us today? The article attempts to answer this question by tracing Bonhoeffer’s theological concerns that led him to ask this question in what he called a religionless age. In the first section of the article, Bonhoeffer’s understanding of this age will be examined. In the second and third sections, the who-question will be explored in light of the parts of his theology where his Christological imperative gains differentiated contours. This article’s contribution does not lie in the different answers that can be given from Bonhoeffer’s own theology, but rather it seeks to understand the question better. In other words, what does this question mean in a religionless age? In the fourth section, Bonhoeffer’s question will be used as a hermeneutical tool. How can a more differentiated understanding of Bonhoeffer’s question, or the theology underlying this question, contribute to a hermeneutic for being church today?